The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: RSD measurement from the LOS-dependent power spectrum of DR12 BOSS galaxies - Gil-Marin, H.; Percival, W. J.; Brownstein, J. R.; Chuang, C. H.; Grieb, J. N.; Ho, S.; Kitaura, F. S.; Maraston, C.; Prada, F.; Rodriguez-Torres, S.; Ross, A. J.; Samushia, Lado; et al. (My University, 2016)
We measure and analyse the clustering of the Baryon Oscillation Spectroscopic Survey (BOSS) relative to the line of sight (LOS), for LOWZ and CMASS galaxy samples drawn from the final Data Release 12. The LOWZ sample contains 361 762 galaxies with an effective redshift of z(lowz) = 0.32, and the CMASS sample 777 202 galaxies with an effective redshift of z(cmass) = 0.57. From the power spectrum monopole and quadrupole moments around the LOS, we measure the growth of structure parameter f times the amplitude of dark matter density fluctuations sigma 8 by modelling the redshift-space distortion signal. When the geometrical Alcock-Paczynski effect is also constrained from the same data, we find joint constraints on f sigma(8), the product of the Hubble constant and the comoving sound horizon at the baryondrag epoch H(z) r(s)(z(d)), and the angular distance parameter divided by the sound horizon DA(z)/r(s)(zd). We find f(z(lowz)) sigma(8)(z(lowz)) = 0.394 +/- 0.062, D-A(zlowz)/r(s)(z(d)) = 6.35 +/- 0.19, H(z(lowz)) r(s)(z(d)) = (11.41 +/- 0.56) 103 km s(-1) for the LOWZ sample, and f( z(cmass)) sigma 8(z(cmass)) = 0.444 +/- 0.038, D-A(z(cmass))/r(s)(z(d)) = 9.42 +/- 0.15, H(z(cmass)) r(s)(z(d)) = (13.92 +/- 0.44) 103 km s-1 for the CMASS sample. We find general agreement with previous BOSS DR11 measurements. Assuming the Hubble parameter and angular distance parameter are fixed at fiducial +/- cold dark matter values, we find f( zlowz) sigma(8)( z(lowz))= 0.485 +/- 0.044 and f(z(cmass)) sigma(8)(z(cmass))= 0.436 +/- 0.022 for the LOWZ and CMASS samples, respectively.
Citation: Gil-Marin, H., Percival, W. J., Brownstein, J. R., Chuang, C. H., Grieb, J. N., Ho, S., . . . Zhao, G. B. (2016). The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: RSD measurement from the LOS-dependent power spectrum of DR12 BOSS galaxies. Monthly Notices of the Royal Astronomical Society, 460(4), 4188-4209. doi:10.1093/mnras/stw1096
Keywords: Galaxies: Haloes; Cosmological Parameters; Cosmology: Theory; Large-Scale Structure Of Universe; Digital Sky Survey; Redshift Space Distortions